A slot-based approach to optimise freeway traffic using Intelligent Vehicles - Marinescu, Dan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2014)
Over the last decades, the increase in demand for road transportation has traditionally been matched by an expansion of the road network to prevent or reduce traffic congestion. This approach is unsustainable in the long term. A sustainable solution requires more efficient use of the existing road network by deploying so-called Intelligent Transportation Systems (ITS). Present day ITS implementations are generally responsible for controlling road access, incident detection and mitigation, predicting traffic conditions and providing route guidance, with the vast majority of these systems being deployed as part of the road infrastructure.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin